Question:

Let f(x) = (1 + 4x^2)(x - x^2). a)Find the derivative by using the Product Rule. f'(x) =_________ b)Find the derivative by multiplying first. f'(x) =_________ c)Do your answers agree? 1)Yes 2)No

Let f(x) = (1 + 4x^2)(x - x^2).

a)Find the derivative by using the Product Rule.
f'(x) =_________
b)Find the derivative by multiplying first.
f'(x) =_________
c)Do your answers agree?
1)Yes
2)No

Let f(x) = (1 + 4x^2)(x - x^2). a)Find the derivative by using the Product Rule. f'(x) =_________ b)Find the derivative by multiplying first. f'(x) =_________ c)Do your answers agree? 1)Yes 2)No

More Questions on Application of derivatives

View all